The Effect of Problem-Based Learning Based Ethnoscience on Science Literacy Ability of Elementary School - Ilmiatul Hidayanti; Fitria Wulandari (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research aims to determine the effect of problem-based learning based on ethnoscience on science literacy skills at SDN Bringinbendo 2. The Ethnoscience-based PBL model is a learning model that can develop students' scientific literacy abilities. This study used a quantitative approach with experimental methods with the type of research one group pre-test-post-test. The sample in this study was V-grade students at SDN Bringinbendo 2, which consisted of 21 students. Data collection in this study used a pre-test and post-test. Data were analyzed using a hypothesis t-test and the Eta Squared test. The results of the research hypothesis test were t-sample t-test, Sig. (2-tailed) ie 0.00 <0.05 so there is a significant effect (H₁ is accepted and H₀ is rejected). So it can be seen that the ethnoscience-based PBL model influences the scientific literacy skills of class V at SDN Bringinbendo 2. In the results of the eta-squared test, there is an increase with a vulnerable score of t > 0.14, indicating an influence of the big one. Using the Ethnoscience-based PBL model can improve the scientific literacy skills of V-grade students.